Poland : BCBS-IADI Core Principles for Effective Deposit Insurance Systems - World Bank (Washington, DC, 2014)
During February 19-March 4, 2013 an assessment under the International Monetary Fund (IMF)/World Bank Financial Sector Assessment Program (FSAP) was conducted for the Republic of Poland. Poland's financial system has been expanding rapidly and remains dominated by banks. The total assets of the financial system grew from 86 percent of Gross Domestic Product (GDP) in 2005 to 124 percent of GDP in 2012. The banking system is dominated by a handful of foreign-owned banks. They control about 65 percent of the sector's assets-a sizeable proportion, but lower than in the Czech Republic, Hungary, and Slovakia. The Polish banking system is well capitalized and liquid. In aggregate, capital adequacy reached 14.7 percent, 90 percent of which is tier capital. Banks' profits in 2011 and 2012 were historically high, and regulations restricting dividend payouts aided capital building. Regulatory and supervisory efforts have helped improve the resilience of the banking system, but the economic slowdown will pose some challenges for banks. Poland's regulatory, supervisory, and resolution frameworks are influenced by developments at the European Union (EU) level. As a member of the EU, Poland is obliged to comply with EU directives when they come into force. Poland is expected to be in line with the changed EU Directives on deposit insurance systems, and on the new EU Directive on bank recovery and resolution. The ongoing modernization of Poland's financial system and challenging macroeconomic environment pose challenges to the supervisory and regulatory system. Accounting and disclosure regimes support the ability of the supervisor and deposit insurer to adequately evaluate the health of individual banks and the banking system as a whole.